2014
DOI: 10.1111/pai.12257
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor fungi and child asthma health service attendances

Abstract: Asthma is a significant global public health issue. Severe asthma exacerbations can be triggered by environmental factors and require medical care from health services. Although it is known that fungal exposure may lead to allergic sensitization, little is understood about its impact on asthma exacerbations. This review aims to examine whether outdoor fungi play a significant role in child asthma exacerbations. Systematic search of seven electronic databases and hand searching for peer-reviewed studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 59 publications
(106 reference statements)
1
24
2
Order By: Relevance
“…However, the mechanism underlying the AD-induced exacerbation of asthma remains unclear. Several studies have shown that outdoor fungi were associated with an increase of emergency department visits, hospitalizations, and aggravation of asthma symptoms in patients with asthma [1618]. However, according to the results of the present study, heavy exposure to outdoor fungi does not represent a likely cause for the exacerbation of asthma caused by exposure to AD.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, the mechanism underlying the AD-induced exacerbation of asthma remains unclear. Several studies have shown that outdoor fungi were associated with an increase of emergency department visits, hospitalizations, and aggravation of asthma symptoms in patients with asthma [1618]. However, according to the results of the present study, heavy exposure to outdoor fungi does not represent a likely cause for the exacerbation of asthma caused by exposure to AD.…”
Section: Discussioncontrasting
confidence: 50%
“…Although AD has been suggested to exert allergic and toxic effects, it remains uncertain as to which components of AD are associated with the exacerbation of asthma. Several studies have reported that outdoor fungi can increase emergency department visits and hospitalization for asthma exacerbation and can aggravate asthma symptoms [1618]. AD has also been shown to carry microbial agents [19] and a few studies have reported increases in the abundance of several fungal taxa during heavy AD days [2022].…”
Section: Introductionmentioning
confidence: 99%
“…Stratifying patients with severe asthma into 2 groups on the basis of their response to fungal exposure reveals that the patients who respond to fungal allergens have earlier onset symptoms and require more oral steroid therapy than do those who do not and experience a greater number of asthma exacerbations 41, 42, 43. GWAS data predict that elevated ORMDL3 expression increases the risk of severe asthma and asthma exacerbations; thus, given the association between ORMDL3 and Alternaria -induced AHR revealed in the present study, it would be pertinent to determine whether SNPs in the 17q21 locus are associated with severe fungal-associated asthma phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Alternaria or Cladosporium spp sensitization was associated with asthma severity in the European Community Respiratory Health Survey. Furthermore, a recent paper has shown that fungal sensitization in children with persistent asthma is associated with disease severity (113) and a 2014 review has shown increasing evidence that sensitized asthmatic children may be susceptible to asthma exacerbations when exposed to outdoor fungal spores and that the severity of exacerbation may vary with different fungi species (114).…”
Section: Outdoor Indoor and Food Allergensmentioning
confidence: 99%